ANALISIS HAK DAN KEWAJIBAN GURU DALAM UNDANG-UNDANG NOMOR 14 TAHUN 2005 (STUDI KASUS GURU HONORER MATA PELAJARAN PAI JENJANG SD NEGERI DI KAPANEWON SEYEGAN, KABUPATEN SLEMAN) - Fathin, Arif Faisal (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2023)
This article aims to find out how the rights and obligations of PAI honorary teachers at the elementary level in KapanewonSeyegan are in accordance with Law no. 14 of 2005. The research method in this article is a qualitative descriptive method with data collection through semi-structured interviews and participatory observation. The results of this study show; The rights that have not been obtained by honorary teachers are; the right to a decent income, the right to welfare security, the right to strong legal protection for honorary teachers, the right to guarantee safety, the right to have the opportunity to improve academic qualifications through PPG. While the rights obtained are; the right to improve teacher competence through PAI KKG activities, the right to use facilities and infrastructure for teaching and learning activities, the right to provide an assessment in the form of awards, graduations and sanctions according to the rules of educators, the right to freedom to join professional organizations, the right to determine and develop policies in the KapanewonSeyegan area, the right to receive training and professional development of teachers through PAI KKG activities. In terms of fulfilling their obligations, honorary teachers have carried out their duties comprehensively, in terms of learning planning, conducting quality teaching and learning activities, evaluating learning well, always eager to improve teacher competence, not being objective and discriminatory, supported by a religious moderation program.